PENERAPAN COGNITIVE BEHAVIOR THERAPY DALAM MENGELOLA KECEMASAN PADA SISWA ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) - Ahmad Zaki Ilman Nasution; Netrawati, Netrawati; Zadrian Ardi (Counseling Milenial (CM), 2024)
Children with Attention Deficit Hyperactivity Disorder (ADHD) often experience difficulties in the school environment, especially in terms of concentration, hyperactive behavior and impulsivity. Although most children with ADHD are still served in regular classes, this can hinder students' development, both academically and socially. To support student development, a guidance and counseling approach based on collaboration between teachers, counselors and parents is very important. One intervention that has been proven effective is Cognitive Behavioral Therapy (CBT), which can help ADHD children manage anxiety and impulsive behavior. This research uses a literature review method to explore the application of CBT in managing anxiety in ADHD students, with an analysis of various relevant studies. The research results show that CBT is effective in helping ADHD children overcome the difficulties students face at school and in social interactions, as well as supporting better development. Researchers emphasize the importance of collaboration between educators and counseling personnel to create a supportive environment for children with ADHD.